STUDY OF SEPARATE MOUND GROUP NO. 7 IN THE SOUTHERN SECTION OF THE PALASA-SYRT BURIAL MOUND OF THE 4th-5th cc - Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2016)
This article covers the new materials from the Palasa-Syrt burial mound of the 4th-5th centuries, obtained in 2016 during the excavations of mound group No. 7 including seven mounds. The funeral rites of this group had traditional features. Seven burials out of ten were made in catacombs, and the chambers were located perpendicular to the entrance pit. Two burials were made in shaft-and-chamber graves. Under most mounds there was one burial, except two mounds (1560 and 1565), each of them had two graves - of an adult person and a child. All the burials, except for the two children’s (mound 1560, burial 2; mound 1565, burial 2), were robbed in ancient times, but among the preserved grave goods there are unique articles of women’s dresses (mound 1560, burial 1; mounds 1567, 1568); a man’s military set (mound 1559), objects linked with manifestations of religious beliefs (mound 1567), a collection of various ceramic vessels (mound 1560, burials 1,2; mound 1565, burial 2; mounds 1562; 1568). The burials date back to the last quarter of the 4th - the first half of the 5th cc.